Psychological Condition of Women Who Divorced Due to Husbands’ Infidelity - Vina Witri Astuti; Sri Lestari (Journal An-Nafs: Kajian Penelitian Psikologi, 2022)
The divorce experience of a woman caused by her husband's infidelity will impact her life. This study aimed to understand the psychological impacts of divorced women due to their husbands’’ infidelity. The research used a phenomenological method of qualitative approach. Research participants were five women who experienced a divorce caused by husbands’ infidelity selected using the purposive sampling technique. The age range of the participants was 26 to 38 years. Semi-structured interviews were used to collect the data. The data were analyzed using Interpretative Phenomenological Analysis (IPA). The results of this study showed that the psychological condition of women who divorced because of infidelity included feelings of inferiority and worthless, fear and worry about the future, feelings of sadness and misery, regret and disappointment because the reality was different from expectations, anger, hate and heartache, hopeless, difficulty trusting men because of feeling betrayed. During the infidelity, the husband and wife relationship experienced conflict, which worsened the situation until they decided to divorce. Even after the divorce, the negative psychological conditions were still felt and caused doubts about the self’s ability to be responsible for growing up children and making them happy.